Barbarisms, vices, and incorrectness. The linguistic attitudes perceived in Equivocaciones de los centroamericanos al hablar castellano (1858) by Juan Eligio de la Rocha - Cuadrado, Carmen Martín (2024)
This paper aims to analyze Equivocaciones de los centroamericanos al hablar castellano (1858), collection by Juan Eligio de la Rocha. Moreover, the study allows us to observe the author’s ideology towards the Nicaraguan language in the 19th century. Firstly, Juan Eligio de la Rocha is presented like the pioneer in the study of Nicaraguan language and a follower of the purist movement. Furthermore, the linguistic attitudes are analyzed, followed by a classification of the improprieties according to their linguistic field.